Renormalization and ultraviolet sensitivity of gauge vertices in universal extra dimensions - Ayres Freitas; Daniel Wiegand (Journal of High Energy Physics, 2018)
Abstract When computing radiative corrections in models with compactified extra dimensions, one has to sum over the entire tower of Kaluza-Klein excitations inside the loops. The loop corrections generate a difference between the coupling strength of a zero-mode gauge boson and the coupling strength of its Kaluza-Klein excitation, although both originate from the same higher-dimensional gauge interaction. Furthermore, this discrepancy will in general depend on the cutoff scale and assumptions about the UV completion of the extra-dimensional theory. In this article, these effects are studied in detail within the context of the minimal universal extra dimension model (MUED). The broad features of the cutoff scale dependence can be captured through the solution of the functional flow equation in five-dimensional space. However, an explicit diagrammatic calculation reveals some modifications due to the compactification of the extra dimension. Nevertheless, when imposing a physical renormalization condition, one finds that the UV sensitivity of the effective Kaluza-Klein gauge-boson vertex is relatively small and not very important for most phenomenological purposes. Similar conclusions should hold in a larger class of extra-dimensional models besides MUED.